2016
DOI: 10.17957/ijab/15.0161
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antiplasmodial Activity of Crude Ethanolic and N-hexane Extracts of Moringa oleifera Leaves

Abstract: This study was carried out to determine the antiplasmodial activity of leaves of Moringa oleifera. Cold extraction method was carried out on grinded leaves to prepare the crude ethanolic and n-hexane extracts. Mice models (Mus musculus) were passaged with chloroquine resistant Plasmodium berghei, which are similar in morphology, physiology and life cycle to P. falciparum that infect humans. Stock solutions of 5 mg/mL 5% DMSO were prepared and the extracts were administered at different treatment concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
7
1
1
Order By: Relevance
“…The extract gave a significant (P<0.05) non dose dependent reduction in the mean percentage parasitemia levels. This current finding contradicts the research result reported by Olashinde [32] involving Moringa oleifera seed which showed that the in vivo anti-malarial reduction of the mean % parasitemia was dose dependent for the n-hexane and ethanol extracts ( Table 3).…”
Section: Resultscontrasting
confidence: 99%
“…The extract gave a significant (P<0.05) non dose dependent reduction in the mean percentage parasitemia levels. This current finding contradicts the research result reported by Olashinde [32] involving Moringa oleifera seed which showed that the in vivo anti-malarial reduction of the mean % parasitemia was dose dependent for the n-hexane and ethanol extracts ( Table 3).…”
Section: Resultscontrasting
confidence: 99%
“…Empat spesies Plasmodium yang menginfeksi manusia, yaitu P. falciparum (menyebabkan malaria tropika), P. malariae (menyebabkan malaria kuartana), P. vivax dan P. ovale (menyebabkan malaria tersiana). Namun dari keempat spesies tersebut, P. falciparum yang paling patogen dan bertanggungjawab untuk hampir semua kematian akibat malaria [5].…”
Section: Pendahuluanunclassified
“…Other studies have shown that Moringa possess a variety of properties including anti-diabetic, anti-inflammatory, anti-cancer [16], anti-ischemic [17] and even anti-plasmodial properties [15]. Of interest to the present study, Moringa has been shown to possess immune boosting properties [18], and potent curative/ suppressive effects on parasite burden in Plasmodium infection [8,19,20].…”
mentioning
confidence: 91%
“…For instance, a study performed by Dondee et al showed a dose dependent suppressive effect on parasite growth of up to 90% and an 80% reduction in parasite burden [19]. Olasehinde et al [20] also observed this suppressive effect in their study that employed both crude ethanolic and an n-hexane Moringa leaf extracts. They found that the crude ethanolic extract inhibited parasitaemia by 74.7 to 95.6% and n-hexane extract inhibited by 59.3 to 87.9%.…”
mentioning
confidence: 95%